FRI0423 Antibodies to type ii collagen: a novel tool for the spondyloarthritis diagnosis?. (15th June 2017) - Vinci, C; Infantino, M; Pozzilli, P; Grossi, V; Manfredi, M; Bandinelli, F; Gobbi, F Li; Damiani, A; Strollo, R; Benucci, M; Nissim, A
Abstract : Background: Spondyloarthritis (SpA) are an inflammatory joint disease with chronic, progressive, axial inflammation of the spine and the sacroiliac joints. Diagnosis of SpA is done criteria by clinical symptoms, radiology and MRI or ultrasound following ASAS criteria. AS is similar to rheumatoid arthritis (RA) and psoriatic arthritis (PsA) as they are all inflammatory joint disease. Nevertheless they show considerable different pathology. [1] Objectives: The aim of our study is to test whether a novel assay that we developed for RA can be used for SpA diagnosis. We have previously showed that antibodies to oxidative post-translationally modified collagen type II (oxPTM-CII) are present specifically in RA patients whether ACPA positive or negative. [2] Our study intends to investigate the reactivity to oxPTM-CII in SpA patients in comparison to early undifferentiated arthritis (EUA) and PsA patients. Methods: oxPTM-CII were generated using ribose and various reactive oxidants, and then they were analysed by SDS-PAGE. Binding to native and oxPTM-CII was evaluated by ELISA and Western Blotting. We used a cohort of sera from 67 patients with SpA, 54 patients with PsA, 49 patients with EUA. As control we used 19 patients with fibromyalgia (FM) and 70 healthy subjects. The specificity of the binding was further assessed by competitive ELISA and western blot. Results: We detected stronger reactivity to SpA compared to PsA and even EUA serum samples. Hence specific binding to oxPTM-CII was seen in the 52% of SpA sera compared to 12% in PsA and 10% in EUA. There was no binding in samples from FM and healthy individuals. A group of the most reactive SpA samples was evaluated by western blot confirming a strong binding to several fragments or aggregates of oxPTM-CII. Conclusions: For the first time we demonstrated that anti-ROS-CII may become a biomarker for SpA diagnosis. References: J. Braun and J. Sieper, Ankylosing spondylitis. Lancet, vol. 369, no. 9570, pp. 1379–1390, 2007. R. Strollo, F. Ponchel, V. Malmström, P. Rizzo, M. Bombardieri, C. Y. Wenham, R. Landy, D. Perret, F. Watt, V. M. Corrigall, P. G. Winyard, P. Pozzilli, P. G. Conaghan, G. S. Panayi, L. Klareskog, P. Emery, and A. Nissim, Autoantibodies to posttranslationally modified type II collagen as potential biomarkers for rheumatoid arthritis. Arthritis Rheum., vol. 65, no. 7, pp. 1702–12, Jul. 2013. Disclosure of Interest: None declared